2003
DOI: 10.1046/j.1525-1470.2003.20505.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Dyschromicum Perstans in Prepubertal Children

Abstract: Erythema dyschromicum perstans (EDP) is a rare disorder of pigmentation that is most common in Hispanic patients. In adults, EDP has a slow onset and is unlikely to resolve spontaneously. The etiology and clinical course in children is poorly defined. Physical examinations, chart reviews, and telephone interviews were performed for eight pediatric patients with EDP who were followed at Children's Memorial Hospital in Chicago between 1990 and 1998. All the patients available for long-term follow-up (five of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 42 publications
0
46
1
6
Order By: Relevance
“…The condition is most common in Asia and Central and South America, as the majority of the published cases have been from those regions [7][8][9]. Silverberg and colleagues reported that most of the prepubertal patients suffering from Ashy dermatosis were Caucasians (52%) and Hispanics (36%) [10]. There have been two case reports of Indian children with this condition [11,12].…”
Section: Epidemiologymentioning
confidence: 99%
“…The condition is most common in Asia and Central and South America, as the majority of the published cases have been from those regions [7][8][9]. Silverberg and colleagues reported that most of the prepubertal patients suffering from Ashy dermatosis were Caucasians (52%) and Hispanics (36%) [10]. There have been two case reports of Indian children with this condition [11,12].…”
Section: Epidemiologymentioning
confidence: 99%
“…Su inicio suele ser insidioso y rara vez se resuelve en forma espontánea en la edad adulta, aunque en la infancia puede remitir entre 2 y 3 años después de su inicio en la mayoría de los casos 3,21,23 . Este último autor señala que el 52% de los casos en etapa prepuberal se desarrolla en pacientes caucásicos, 36% en hispanos, 4% afroamericanos, 4% asiáticos y 4% no especificado.…”
Section: Clínicaunclassified
“…Se ha probado sin éxito el empleo tópico de corticoides e hidroquinona, mientras que por vía oral tampoco ha sido efectivo el uso de antibióticos, griseofulvina, isoniazida o prednisona, al igual que la luz ultravioleta 23 . En alguna publicación se ha destacado una mejoría considerable con el uso de la clofazimina oral 46,47 ; sin embargo, otros autores no lo han confirmado 48 .…”
Section: Tratamientounclassified
“…Since that time, the disorder has been reported in medical literature under various names: ashy dermatosis, lichen planus pigmentosus, idiopathic eruptive macular pigmentation or los cencientos [2]. Erythema dyschromicum perstans is uncommon in the Caucasian population, and children make up only 8-10% of all EDP patients [4]. Erythema dyschromicum perstans lesions are manifested as asymptomatic greyish ashcoloured, occasionally brown-grey, patches with an erythematous peripheral margin, often barely distinguishable, measuring 1-2 mm in width.…”
Section: Case Reportmentioning
confidence: 99%